2018
DOI: 10.1002/jssc.201800901
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of selected estrogenic endocrine disrupting chemicals and bisphenol A residues in whole milk using fabric phase sorptive extraction coupled to HPLC‐UV detection and LC‐MS/MS

Abstract: A simple and sensitive analytical methodology is developed for rapid screening and quantification of selected estrogenic endocrine disrupting chemicals and bisphenol A from intact milk using fabric phase sorptive extraction in combination with high‐performance liquid chromatography coupled to ultraviolet detection/tandem mass spectrometry. The new approach eliminates protein precipitation and defatting step from the sample preparation workflow. In addition, the error prone and time‐consuming solvent evaporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…It was reported that about 50 homoisoflavoniods were purified and identified by repeated column fractionations [1]. HPLC with diode array detector (DAD) and MS/MS has been developed for rapid isolation and characterization of bioactive components from complex natural products [8–11]. However, information about comprehensive analysis of homoisoflavonoids, especially for minors, in O. japonicus by HPLC–DAD–MS/MS is restricted because of the existence of multicomponents, restriction of detection sensitivity, and coelution of minor and abundant compounds [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that about 50 homoisoflavoniods were purified and identified by repeated column fractionations [1]. HPLC with diode array detector (DAD) and MS/MS has been developed for rapid isolation and characterization of bioactive components from complex natural products [8–11]. However, information about comprehensive analysis of homoisoflavonoids, especially for minors, in O. japonicus by HPLC–DAD–MS/MS is restricted because of the existence of multicomponents, restriction of detection sensitivity, and coelution of minor and abundant compounds [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption capacity of the adsorbents to four structural analogues (17α-E 2 , E 3 , E 1 , and DES; Supporting Information Figure S1) were determined in the same way. Additionally, the imprinting factor (IF) and selectivity coefficient (SC) are defined according to Equations (8) and (9) [29]:…”
Section: Selectivity Adsorption Experimentsmentioning
confidence: 99%
“…Therefore, to ensure food safety and human health, it is necessary to find a simple and efficient analytical method for detecting the residual amount of 17β-E 2 in animal-derived foods. Due to the complexity of food matrices and the low concentration of 17β-E 2 in foods [7,8], effective pretreatment procedures, such as LLE [9], SPE [10], and SPME [11], are usually necessary to enable detection of 17β-E 2 . Of these, SPE is the most widely applied technique in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, designing a sensitive and simple technique to detect BPA would be of special importance. Some analytical procedures have been utilized in determination of BPA such as the gas chromatography‐mass spectrometry (GC‐MS) [5], enzyme‐linked immuno‐sorbent assay (ELISA) [6], HPLC [7], optical sensor [8], fluorescent [9], electrochemical [10], and colorimetric sensors [11]. Although they can provide highly sensitive detection and accurate identification, a majority of the mentioned techniques suffer from a number of limitations like the necessity of the pretreatment stages, very high time consumption, and expensiveness.…”
Section: Introductionmentioning
confidence: 99%